The Use of Cooperative Integrated Reading and Composition (CIRC) to Improve the Students’ Reading Comprehension - Muhsinin; Hery Rahmat; Nurul Lailatul Khusniyah (The Center for Language Development, Mataram State Islamic University., 2022)
In general, most of the students of seventh grade have difficulties in comprehending texts. The objective of this research is to investigate whether the Cooperative Integrated Reading and Composition (CIRC), can improve the students’ reading comprehension at a junior high school in East Lombok Regency. The participants of this research were 25 students. This research was classroom action research which was done in two cycles. The data of this research were collected by conducting observation, test, and documentation, with the criteria of minimum mastery (KKM) of 75. There were two kinds of activities observed namely the teacher’s activity and the students’ activity. The students’ ability was measured by using comprehension test. The result showed that the students successfully met the criteria of minimum mastery. It was indicated from the improvement of the students’ mean score from 67 in Cycle 1 to 81 in Cycle 2. Moreover, the teaching activities improve from 74 in cycle 1 to 94 in cycle 2. Furthermore, the students’ activity also improves from 47 in cycle 1 to 84 in cycle 2. In conclusion, CIRC method was found beneficial to improve the students’ reading comprehension, and to enhance the teaching learning process of reading.